Infrared Testing of CFRP Components: Comparisons of Approaches using the Tanimoto Criterion; NDT in Canada 2015 Conference, June 15-17, 2015, Edmonton - Sojasi S. Saeed; Khodayar F. Fariba; Lopez F. Fernando; Ibarra-Castando C. Clemente; Maldague X. Xavier; Vavilov V. P. Vladimir Platonovich; Chulkov A. O. Arseniy Olegovich (2015, 2015)
Title screen